THE EFFECT OF FINANCIAL SELF-EFFICACY AND LEARNING INTEREST ON STUDENTS' FINANCIAL STATEMENT ANALYSIS ABILITY (Prosiding dan Call Paper Widya Wiwaha, 2024)
This study aims to analyze the factors that influence the ability to analyze student financial statements seen from financial self-efficacy and student interest in learning. Research methods use a quantitative approach. The population chosen for this study is the students of Accounting, Faculty of Economics and Business, State University of Surabaya in the year 2023 amounted to 450 students and sampling of 116 students, with simple random sampling method. The research was conducted by distributing questionnaires and the data analysis technique used was multiple linear regression analysis. The results showed that financial self-efficacy and interest in learning had a positive and significant effect on the ability to analyze student financial statements, with the influence of financial self-efficacy being more dominant than interest in learning. The higher the financial self-efficacy and interest in learning, the higher the level of ability to analyze financial statements.
Keywords: Financial Self-Efficacy; Learning Interest; Financial Statement Analysis Ability